21ST CENTURY SKILLS; THE EFFECT OF PROJECT BASED LEARNING TO FINANCIAL LITERACY ON CHILDREN AGED 5-6 YEARS - Hapsari, Debby Tri; Suryono, Yoyon; Amiliya, Reni (EARR (Educational Administration Research and Review), 2019)
Financial Literacy has a very significant role in determining a person's level of welfare. Financial literacy education must be given from an early age because at this age children are in the golden period so that children can obtain basic financial knowledge and expertise to manage financial resources effectively and wisely by following future needs. At present financial literacy education is still taboo to be taught to young children so that financial literacy education is rarely done either in the family or school environment. To overcome this problem, this study proposes Project Based Learning as an effort to improve the financial literacy abilities of young children, especially children aged 5-6 years. The effectiveness of the Project Based Learning Model was evaluated by designing learning activities carried out through the financial literacy game with the quasi experiment method in 48 children aged 5-6 years. Two variables: Project Based Learning Model and financial literacy. The results showed that there was an increase in financial literacy children aged 5-6 years by 66.67%.